Developing Principal Leadership Assessment Instruments: The Necessity and Challenges - Cheung, Alan C.K. (Science Insights Education Frontiers, 2024)
Principal leadership evaluation and assessment, one of the crucial means for managing and monitoring principals, is of vital significance for principal professional development, the enhancement of principal leadership capability, the optimization of the principal accountability system, and school improvement (Wang, 2016; Han, 2019). At the level of personal growth, principal leadership assessment can provide school leaders with formative and summative feedback, which is beneficial for their professional development (Murphy et al., 2011). At the level of school management, it helps the principal identify the gaps between the existing practices and expected outcomes to make informed decisions for school improvement and development (Goldring et al., 2009); in the meantime, principal leadership assessment with definite results enables other school administrators to understand clearly the goals set for the school and principal, contributing to the development of a climate of collective accountability (Murphy et al., 2011) and the improvement of school governance. Overall, well-designed and properly implemented principal leadership assessment can effectively enhance organizational performance and help select qualified school leaders (Murphy et al., 2011).